2017
DOI: 10.1515/cdbme-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

A user-specific human-machine interaction strategy for a prosthetic shank adapter

Abstract: For people with lower limb amputation, a userspecific human-machine interaction with their prostheses is required to ensure safe and comfortable assistance. Especially during dynamic turning manoeuvres, users experience high loads at the stump, which decreases comfort and may lead to long-term tissue damage. Preliminary experiments with users wearing a configurable, passive torsional adaptor indicate increased comfort and safety achieved by adaptation of torsional stiffness and foot alignment. Moreover, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To take different gait situations and velocities into account, a test cycle that models a typical day of an amputee is generated. This test cycle facilitates the comparison of actuator (Stuhlenmiller et al, 2017 Each combination of gait situation and velocity is conjugated with the corresponding user-specific optimal torsional stiffness and foot alignment.…”
Section: Methods Of Development Processmentioning
confidence: 99%
“…To take different gait situations and velocities into account, a test cycle that models a typical day of an amputee is generated. This test cycle facilitates the comparison of actuator (Stuhlenmiller et al, 2017 Each combination of gait situation and velocity is conjugated with the corresponding user-specific optimal torsional stiffness and foot alignment.…”
Section: Methods Of Development Processmentioning
confidence: 99%
“…Similar to humans, one approach could be to indirectly measure the kinematic interactions between the socket and the underlying bone using marker-based motion capture technology based on assumptions about joint constraints imposed on the system [ 80 ]. Further analysis involves the development and validation of tissue mechanics models using the collected marker-based information [ 81 ]. Moreover, most prostheses do not reproduce concentric muscle action and mainly have a passive function.…”
Section: Future Directionsmentioning
confidence: 99%
“…The gearbox and the engine are connected via the joint connection part (8), and the test bench mount is also mounted here. The load connection (5) for the test bench is connected directly to the output of the gear unit (6). The gearbox is a Harmonic Drive HFUS-2SO with a reduction ratio of 50:1 (6) (Harmonic Drive AG, Limburg an der Lahn, Germany).…”
Section: Structure Designedmentioning
confidence: 99%
“…The application of PEAs in prosthetics has already proven successful with prototypes. The interaction between human and machine can be improved by optimizing the stiffness and foot alignment to the walking situation [6]. Grimmer et al showed in a simulation study that the energy consumption and the peak power are reduced by a PEA for the ankle joint over a range between 0.5 m/s and 2.6 m/s [7].…”
Section: Introductionmentioning
confidence: 99%